If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + -4)(a + 4) = 0 Reorder the terms: (-4 + a)(a + 4) = 0 Reorder the terms: (-4 + a)(4 + a) = 0 Multiply (-4 + a) * (4 + a) (-4(4 + a) + a(4 + a)) = 0 ((4 * -4 + a * -4) + a(4 + a)) = 0 ((-16 + -4a) + a(4 + a)) = 0 (-16 + -4a + (4 * a + a * a)) = 0 (-16 + -4a + (4a + a2)) = 0 Combine like terms: -4a + 4a = 0 (-16 + 0 + a2) = 0 (-16 + a2) = 0 Solving -16 + a2 = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + a2 = 0 + 16 Combine like terms: -16 + 16 = 0 0 + a2 = 0 + 16 a2 = 0 + 16 Combine like terms: 0 + 16 = 16 a2 = 16 Simplifying a2 = 16 Take the square root of each side: a = {-4, 4}
| 6x+12=-58-8x | | 2x-6=-x+15 | | 3x+9x+10=13 | | 5u(2u+3)-2u(u-7)= | | 2x+127=12x-13 | | 3c^2-3c=4c | | 9-7x=84-42x | | 2x-5x=10 | | 5x^2-55x+20=0 | | 10-7x=103-28x | | x^2-16=-13 | | 112-7x=38+17 | | 140-3x=33x+20 | | 25x^2+11=15 | | 3x^2+18x-25=0 | | x^2-7x=7 | | 74+4x=9x+22 | | -119-7x=84-42x | | (x-5)*(x+8)= | | x^2+12x-5=0 | | x^2+(4-3)=26 | | x^2+4-3=5 | | x+5=105 | | -2=-4+3x | | w=f(a+r) | | 4x^2-7x+11=5x+6 | | 27-8(2-Y)=-13 | | 137-7x=29x+17 | | 27-8(2-7)=-13 | | 10x-2=38 | | 6x^2+37+35=0 | | 5y-4=2y+8 |